PEMBERANTASAN KORUPSI DAN KEMAUAN POLITIK DI INDONESIA - Pakpahan, Aknolt Kristian; Triwibowo, Albert; Astari Magetsari, Raden Roro Mirna (Jurnal Pertahanan dan Bela Negara, 2018)
The problem of corruption is strongly rooted in Indonesia and became a problematic issue for Indonesia. Corruption that is also done by law enforcement officers is believed to have undermined the authority of the government not only in domestic but also in international scale. Systemic impact of corruption touches not only the economy sector as a strong pillar of the country's development but also touches the human spirit as part of the national development process. To overcome the problem of corruption, there must be a strong political will from the government that can be implemented in government policy such as promoting exemplary conduct and modest lifestyle, signing the integrity pact, creating an effective punishment, promoting a clear division and synergy among government agencies, establishing the one roof administration in the long run, and introducing an anti-corruption education early on. Â  Keywords: corruption, problems of fighting corruption, and political will.